Efficacy of trabectedin in malignant solitary fibrous tumors: a retrospective analysis from the French Sarcoma Group. Issue 1 (December 2015) - Khalifa, J.; Ouali, M.; Chaltiel, L.; Le Guellec, S.; Le Cesne, A.; Blay, J-Y; Cousin, P.; Chaigneau, L.; Bompas, E.; Piperno-Neumann, S.; Bui-Nguyen, B.; Rios, M.; et al.
Abstract Background Advanced malignant solitary fibrous tumors (SFTs) are rare soft-tissue sarcomas with a poor prognosis. Several treatment options have been reported, but with uncertain rates of efficacy. Our aim is to describe the activity of trabectedin in a retrospective, multi-center French series of patients with SFTs. Methods Patients were mainly identified through the French RetrospectYon database and were treated between January 2008 and May 2013. Trabectedin was administered at an initial dose of 1.5 mg/m2, q3 weeks. The best tumor response was assessed according to the Response Evaluation Criteria In Solid Tumors 1.1. The Kaplan–Meier method was used to estimate median progression-free survival (PFS) and overall survival (OS). The growth-modulation index (GMI) was defined as the ratio between the time to progression with trabectedin (TTPn ) and the TTP with the immediately prior line of treatment (TTPn-1 ). Results Eleven patients treated with trabectedin for advanced SFT were identified. Trabectedin had been used as second-line treatment in 8 patients (72.7 %) and as at least third-line therapy in a further 3 (27.3 %). The best RECIST response was a partial response (PR) in one patient (9.1 %) and stable disease (SD) in eight patients (72.7 %). Disease-control rate (DCR = PR + SD) was 81.8 %. After a median follow-up of 29.2 months, the median PFS was 11.6 months (95 % CI = 2.0; 15.2 months) and the median OS was 22.3 months (95 % CI = 9.1 months; not reached). The median GMI was 1.49 (range: 0.11–4.12). Conclusion Trabectedin is a very promising treatment for advanced SFTs. Further investigations are needed.